The poetic image: an exploration of memory and making in architecture and film - Sturich, Matthew Alexander (Kansas State University, 2005)
Film allows a different way of looking at space than architecture. It gives easier access to the set-up world of the narrative. The narrative is the story of what happens in the spaces—what the idea of the space is—its ritual. Using the media of film presents a better understanding of a world through the projected images to the designer and viewers. A short film—Poesis—was made to provoke poetic images. The film was used to construct architecture through film, developing a process of making and a more complete understanding of architecture. Each space was treated as a repository for a poetic image. The poetic image is art, a connection to memory, and viewed through materiality. The poetic image allows a relationship with reality, while giving a new awareness of the world at hand. Art is defined as something that sets up a world for someone to enter. Film and architecture both set up a world that is created through memory and material, thus art. Memory is a narrative that does not depend on time, but instead movement through space. Memory allows for empathy from the viewer, creating a connection with the world and characters in it. Materials create surfaces. Surfaces meet at corners and the meeting of these surfaces create a container for space. The space that these surfaces hold give new memories that are poetic images. Andrei Tarkovsky wrote, “Poetry is an awareness of the world, a particular way of relating to reality.” The poetic image is understood as a better understanding, or awareness, of the world we dwell in. Poesis was created as art, setting up a world for someone to enter; not only the character, but the audience as well. The character’s memory of space was taken away in order to purge the desensitization created from the bombardment of images of our culture, and to present the character with new memories of space. Giving these new, simpler notions of space allowed for a more innocent view and awareness of his surroundings. Using these things together created the poetic image of the film—a new awareness and understanding of the world we dwell within. The process of constructing architecture through film allowed for a more complete image of the building being designed. Film is an art that sets up the world that the narrative of the story takes place in with clear and concise juxtaposed images. The process of constructing was a different way of treating the space so it contained the poetic image. The film became a tool of communication for the architecture and its poetics. A more complete understanding of what the space was emerged by looking through the eyes of a filmmaker. A new sense of space developed through this process of making.
Keywords: Poetic image; Architecture; Film; Memory; Process; Architecture (0729)